Influence of paravertebrals miorelaxation on cerebral hemodynamics of sportsmen - D.V. Syshko (H.S. Skovoroda Kharkov National Pedagogical University, 2014)
Purpose: Paravertebrals miorelaxation was the complex of exercises in a water environment directed on the decline of tone of paravertebral muscles. Material: Before and after it was used of paravertebrals miorelaxation registered the indexes of reoentsefalografics at the sportsmen engaged in the Greek-Roman fight (n=22) by football (n=24) and heavy athletics (n=25). Results : The changes, that have been determined at the wrestlers, was in the form of increasing tone of large (increase TRF, TGRР, decreased ADR) and medium (decreased Т1, Т2) arteries of the brain, decreased tone of the small arteries. Paravertebral myorelaxation of weightlifters caused them changes in the form of increasing tone of the great vessels (increase Т3), decreased tone of large and medium-sized arteries of the brain (increase АDR, Т2), increasing the tone of the small arteries (increase АI, DI). Reliable changes in cerebral hemodynamics have not been established at football players. Conclusions: The obtained data indicate that there are different mechanisms of adaptation in the brain blood vessels under conditions of the paravertebral miorelaxation. These differences are predetermined by two main factors: the functional state of the cardiovascular system in general and the functional states of the system of regulation of cerebral hemodynamics.